Microchemical system for simultaneous measurement of surface-enhanced Raman scattering and electrochemical reactions - Shunya Saegusa; Masayuki Naya; Takao Fukuoka; Miyuki Tabata; Koji Sumitomo; Akinobu Yamaguchi (Scientific Reports)
Abstract Electrochemical reactions have been extensively studied and used in various fundamental research and engineering applications such as electroplating, surface treatment, secondary batteries, and fuel cells because they are scalable, economically viable, and practical processes. Research on electrochemical reactions is ongoing because they still contain unknown phenomena. In particular, the ability to conduct reactions at interfaces while precisely controlling non-equilibrium chemical reaction states electrically contributes to the analysis of reaction mechanisms and industrial applications. In this study, we fabricated a gold nanofève structure as a working electrode and traced the chemical reaction processes during electrochemical reactions by simultaneous measurement of surface-enhanced Raman scattering (SERS) spectra. In addition to confirming the reattachment of 4-mercaptobenzoic acid by electrochemical manipulation, the redox reactions and formation of copper nanoparticles in aqueous copper acetate solutions were tracked by in situ SERS measurements while controlling electrochemical reactions. This enabled in situ real-time SERS measurements on the surface of the working electrode in the microsystem during electrochemical reactions. The developed system can be used to measure non-equilibrium chemical reaction dynamics at solid–liquid interfaces to explore related phenomena.